2014
DOI: 10.1099/mic.0.078279-0
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the complete genome sequence of Advenella mimigardefordensis strain DPN7T and novel insights in the catabolism of the xenobiotic polythioester precursor 3,3′-dithiodipropionate

Abstract: Advenella mimigardefordensis strain DPN7 T is a remarkable betaproteobacterium because of its extraordinary ability to use the synthetic disulfide 3,39-dithiodipropionic acid (DTDP) as the sole carbon source and electron donor for aerobic growth. One application of DTDP is as a precursor substrate for biotechnically synthesized polythioesters (PTEs), which are interesting nondegradable biopolymers applicable for plastics materials. Metabolic engineering for optimization of PTE production requires an understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 115 publications
(176 reference statements)
1
28
0
Order By: Relevance
“…In the study performed by Antoine et al [15], it was shown that the citrate uptake SBP BctC from B. pertussis is not only involved in citrate transport but also plays a role in gene regulation, interacting with the two-component system BctDE in order to modulate expression levels of the bctCBA system itself. The few TTT SBPs characterised so far seem to bind to substrates containing at least two or more carboxylate groups, as observed with the citrate binding TctC [33], the terephthalate-binding protein TphC [13], the disulphide 3,3 0dithiodipropionic acid (DTDP)-binding protein TctC [20] and the sulpholactate-binding protein SlcH [19], where a sulphate group gives a similar polarity to the molecule as a carboxylate group would, raising the question as to whether this would be a prevalent characteristic of this family. Although a two-component system is directly upstream of adpC on the opposite strand, bioinformatics analysis showed that the sensor domain in RPA4513, contains no transmembrane regions and encodes for a histidine kinase of the HWE family, which are soluble in the cytoplasm and are known to respond to light stimuli [30].…”
Section: Discussionmentioning
confidence: 84%
“…In the study performed by Antoine et al [15], it was shown that the citrate uptake SBP BctC from B. pertussis is not only involved in citrate transport but also plays a role in gene regulation, interacting with the two-component system BctDE in order to modulate expression levels of the bctCBA system itself. The few TTT SBPs characterised so far seem to bind to substrates containing at least two or more carboxylate groups, as observed with the citrate binding TctC [33], the terephthalate-binding protein TphC [13], the disulphide 3,3 0dithiodipropionic acid (DTDP)-binding protein TctC [20] and the sulpholactate-binding protein SlcH [19], where a sulphate group gives a similar polarity to the molecule as a carboxylate group would, raising the question as to whether this would be a prevalent characteristic of this family. Although a two-component system is directly upstream of adpC on the opposite strand, bioinformatics analysis showed that the sensor domain in RPA4513, contains no transmembrane regions and encodes for a histidine kinase of the HWE family, which are soluble in the cytoplasm and are known to respond to light stimuli [30].…”
Section: Discussionmentioning
confidence: 84%
“…1.1.1.100) and a putative malate/ l ‐lactate dehydrogenase (E.C. 1.1.1.27) also putatively involved in carbohydrate metabolism, are located (Wübbeler et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…T (56% identical amino acids) and V. paradoxus TBEA6 (55% identical amino acids) were also found (17,18,51,52). The amino acid sequence of CdoA shared 83% identical amino acids with the type I cysteine dioxygenase from Cupriavidus pinatubonensis (formerly R. eutropha) JMP 134.…”
Section: Resultsmentioning
confidence: 86%
“…The investigated bacterial enzymes showed high specificity for cysteine, and the kinetic properties were very similar to those of the Cdo from rat, indicating that these proteins were indeed bona fide Cdos (11). During our studies on the microbial catabolism of TDP and DTDP, we identified genes coding for Cdo homologues in V. paradoxus TBEA6 (17,52), R. eutropha H16 (17), and A. mimigardefordensis DPN7 T (18,51). However, the putative Cdos from A. mimigardefordensis …”
Section: Discussionmentioning
confidence: 98%